Role of drowsy driving in traffic accidents: A questionnaire survey of Thai commercial bus/truck drivers - Manoon Leechawengwongs (2018)
Objective: The authors assessed the relationship between traffic accidents and drowsiness. Material and Method: A self-answered questionnaire survey of 4331 commercial bus/truck drivers was done. Result: Sixty-nine percent of the drivers reported accidents and one third of these accidents was attributable to drowsiness. Drowsy driving and microsleeps were experienced by 75% and 28% of drivers respectively. Forty-five percent of drivers had excessive daytime sleepiness based on the Epworth Sleepiness Scale (ESS score ≥ 11). This excessive daytime sleepiness was strongly associated with feeling drowsy, microsleeps, and accidents. The major causes of drowsiness were sleep deprivation (90%), medications that caused sleepiness (78%), drinking alcohol the previous night (23%), and chronic loud snoring with or without obesity (17%). 61% of drivers worked longer than 12 hours with no days off. The feeling of drowsiness at the wheel was also closely related to long hours of driving (> 4 hours). Countermeasures that drivers used to keep them awake were talking to someone, drinking coffee or caffeinated-energy drinks, chewing snacks or gum and pulling over to have a nap. Conclusion: There is a strong relationship between accidents and drowsiness in commercial bus/truck drivers. The main cause of drowsiness was sleep deprivation. The authors hope that this information will help the public authority develop a policy to reduce the traffic accidents attributable to drowsy driving in commercial bus/truck drivers.